2020
DOI: 10.1186/s13046-020-1539-7
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the serotonin agonist Tegaserod as an anticancer agent in melanoma: molecular mechanisms and clinical implications

Abstract: Background: New therapies are urgently needed in melanoma particularly in late-stage patients not responsive to immunotherapies and kinase inhibitors.Methods: Drug screening, IC50 determinations as well as synergy assays were detected by the MTT assay. Apoptosis using Annexin V and 7AAD staining was assessed using flow cytometry. TUNEL staining was performed using immunocytochemistry. Changes in phosphorylation of key molecules in PI3K/Akt/mTOR and other relevant pathways were detected by western blot as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…A considerable number of preclinical studies are investigating other novel targets for overcoming BRAF inhibitor resistance. These include combining BRAF and/or MEK inhibitors with inhibitors of pre-mRNA splicing (to counteract resistance caused by BRAF splicing) [ 251 ], BH3-mimetics [ 252 , 253 ], BCL2 inhibitors [ 254 ], mitochondrial-targeted agents [ 255 , 256 ], inhibitors of p90 ribosomal S6 kinases [ 257 , 258 ], pro-caspase activating compounds [ 259 ], Rho kinase 1 (ROCK1) inhibitors [ 260 ], protein kinase Cδ inhibitors [ 261 ], tubulin inhibitors [ 262 ], ErbB2 or ErbB3 inhibitors [ 222 , 263 , 264 ], activators of the liver-X nuclear hormone receptor [ 265 ], an antibody conjugate targeting the endothelin B receptor [ 266 ], monoclonal antibodies against chondroitin sulfate proteoglycan 4 [ 267 ], inhibitors of sterol regulator element binding protein I (SREBP-1) [ 268 ], copper chelators [ 269 ], polo-like 3 kinase inhibitors (including in models of BRAF + MEK inhibitor resistance) [ 270 , 271 ], anti-nodal antibodies [ 272 ], PAK1 inhibitors [ 273 ], GLI1/2 inhibitors [ 274 ], inhibitors of IQ motif-containing GTPase activating protein 1 (IQGAP1) [ 275 ], serotonin agonists [ 276 ], CK2 inhibitors [ 277 ], p53 activators [ 278 ], metformin [ 279 ], statins [ 280 ], non-steroidal anti-inflammatory drugs [ 281 ], mibefradil [ 282 ], hydroxychloroquine (an autophagy inhibitor) [ 83 ], and A100 (a reactive oxygen species-activated prodrug) [ 283 ].…”
Section: Resultsmentioning
confidence: 99%
“…A considerable number of preclinical studies are investigating other novel targets for overcoming BRAF inhibitor resistance. These include combining BRAF and/or MEK inhibitors with inhibitors of pre-mRNA splicing (to counteract resistance caused by BRAF splicing) [ 251 ], BH3-mimetics [ 252 , 253 ], BCL2 inhibitors [ 254 ], mitochondrial-targeted agents [ 255 , 256 ], inhibitors of p90 ribosomal S6 kinases [ 257 , 258 ], pro-caspase activating compounds [ 259 ], Rho kinase 1 (ROCK1) inhibitors [ 260 ], protein kinase Cδ inhibitors [ 261 ], tubulin inhibitors [ 262 ], ErbB2 or ErbB3 inhibitors [ 222 , 263 , 264 ], activators of the liver-X nuclear hormone receptor [ 265 ], an antibody conjugate targeting the endothelin B receptor [ 266 ], monoclonal antibodies against chondroitin sulfate proteoglycan 4 [ 267 ], inhibitors of sterol regulator element binding protein I (SREBP-1) [ 268 ], copper chelators [ 269 ], polo-like 3 kinase inhibitors (including in models of BRAF + MEK inhibitor resistance) [ 270 , 271 ], anti-nodal antibodies [ 272 ], PAK1 inhibitors [ 273 ], GLI1/2 inhibitors [ 274 ], inhibitors of IQ motif-containing GTPase activating protein 1 (IQGAP1) [ 275 ], serotonin agonists [ 276 ], CK2 inhibitors [ 277 ], p53 activators [ 278 ], metformin [ 279 ], statins [ 280 ], non-steroidal anti-inflammatory drugs [ 281 ], mibefradil [ 282 ], hydroxychloroquine (an autophagy inhibitor) [ 83 ], and A100 (a reactive oxygen species-activated prodrug) [ 283 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tegaserod also reduces the tumor volume in the mouse melanoma model. However, tegaserod mediates this action through a serotonin-independent signaling mechanism, where it blunts the phosphorylation of S6 through inhibition of the PI3/Akt/mTOR pathway 122 .…”
Section: Melanomamentioning
confidence: 99%
“…Studies have shown that 5-hydroxytryptamine plays a mitogenic role in colon cancer cells, and 5-hydroxytryptamine 4-receptor is significantly expressed in both colon cancer tissue and cells ( 26 ). Tegaserod maleate has been shown to exert anticancer activity by inducing apoptosis in melanoma cells ( 27 ), and it has been identified as a JAK/STAT3 signal inhibitor, impeding the growth of a variety of cancer cells, including lung cancer, prostate cancer, colon cancer, and cervical cancer ( 28 ). JAK/STAT3 pathway also plays an important role in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%